A smoking cessation induction intervention via virtual reality headset during a dental cleaning: protocol for a randomized controlled trial - B. Borrelli; R. Endrighi; M. M. Jurasic; H. Hernandez; E. Jones; J. Ospina; H. J. Cabral; L.M. Quintiliani; S. Werntz (BMC, 2022)
Abstract Background Effective smoking cessation programs exist but are underutilized by smokers, especially by disadvantaged smokers. Cessation interventions in dental settings have been shown to be effective, but are not consistently delivered due to provider burden and lack of training, especially on how to counsel smokers who are not motivated to quit. Methods This study is a 2-arm, phase III longitudinal randomized controlled efficacy trial to motivate utilization of evidenced based treatments (EBTs) for smoking cessation (e.g., state quitline, clinic-based counseling, the National Cancer Institute's text message program, and pharmacotherapy). Patients attending an urban dental clinic (n = 376) will be randomized to an intervention group (INT; smoking cessation induction video delivered via VR headset during their teeth cleaning, brochure about EBTs, and a 4-week text message program) or control group (CTRL; relaxation video delivered via VR headset during teeth cleaning, the same brochure as INT, and assessment-only text messages). Assessments will occur at baseline, immediately after the clinic appointment, one-month post-appointment and 3-and 6 months later. We hypothesize INT will be more likely to contact EBTs vs CTRL and have greater utilization rates of EBTs. Secondary objectives are to test the efficacy of INT on point-prevalence smoking abstinence, quit smoking attempts, and motivation to quit vs. CTRL. Discussion Incorporating smoking cessation into a dental clinic visit and targeting all smokers, regardless of motivation to quit, provides proactive reach to cigarette smokers who otherwise may not seek treatment for smoking. Trial registration NCT04524533 Registered August 24, 2020.